STUDI AWAL KARAKTERISTIK TEMPERATUR DAN TEKANAN PADA ALIRAN SIRKULASI ALAM DI FASILITAS UJI UNTAI FASSIP-02 MENGGUNAKAN SIMULASI CFD - Ainur Roidi Rosidi (Jurnal Ilmiah Teknik Mesin POROS, 2018)
TFASSIP-02 loop is a test facility that is used for research and development of safety technologies for future nuclear power plants based on natural law. This test facility is designed to study natural circulation phenomena caused by differences in fluid density due to temperature differences in the one-phase heat dissipation system during the simulation of heat removal from the reactor core when an accident occurs. FASSIP-02 loop consists of piping components, water heating tanks, water cooling tanks and expansion tanks. The purpose of this study was to understand the conditions of temperature change and pressure of water working fluid based on temperature changes in the heater section which were simulated on the loop geometry FASSIP-02. The research method was carried out in a simulation of Computational Fluid Dynamics using FLUENT 6.3 software. The working fluid in the FASSIP-02 loop uses water with a temperature of 27°C, the flow rate is varied 0.3 m/s and 0.45 m / s, while the temperature in the heating section is 70°C. CFD simulation results show that the increase in the working fluid temperature of the water with a flow rate of 0.3 m/s after passing through the heating section is 39°C, while the temperature increase of the working fluid of the water with a flow rate of 0.45 m/s is 36.6°C. Pressure drops at flow rates of 0.3 m/s and 0.45 m/s each occur in water working fluid before entering through WHT and after passing through the heating section.